The Nutritional Problems of Adolescents among the Traditional Community of Suku Anak Dalam in the Working Area of Pematang Kabau Health Center, Sarolangun - Sari, Mila; Merita, Merita; Wulansari, Arnati; Faridah, Faridah; Prabowo, Dyan Heru (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Adolescents in traditional community of Suku Anak Dalam (SAD) are a group that susceptible to experiencing nutritional problems and their nutritional status needs to be considered, because it is a transitional period from childhood to adulthood who live as marginalized. Objectives: This study aims to know the nutritional problems of adolescents among the traditional community of SAD in the working area of the Pematang Kabau Health Center, Sarolangun District. Methods: This study used a cross sectional study design which was conducted in the working area of Pematang Kabau Health Center in July until August 2020. The sample in this study was 30 adolescents with a purposive sampling. Measuring instruments used include microtoice, scales and 2 times 24-hours food recall questionnaire. Data were collected by conducting guided interviews using a questionnaire and direct measurement of nutritional status. The data analysis used univariate analysis. Results: The results showed that a large proportion SAD adolescents have normal nutritional status (83.3%), poor eating habits (56.7%), adequate levels of macronutrients are deficits (80%), no food taboo (76.7%), and parental education is low (100%). Conclusions: Based on the results of the study, it can be concluded that there are still nutritional problems in adolescents with SAD, especially in the aspects of consumption and eating habits. Therefore, it is hoped that nutrition and health workers will be active in providing regular education to SAD adolescents so as not to cause nutritional problems